Metodologi Historiografi Muhammad bin Jarir ath-Thabari dalam Tārīkh al-Rusul wa al-Mulūk: Antara Tradisi Hadis dan Konstruksi Sejarah Islam Klasik - Ahmad Syafi’I Mufadzilah Riyadi (Social Science Academic, 2026)
This article examines the historiographical methodology of Muhammad bin Jarir al-Ṭ abarī in Tārīkh al-Rusul wa al-Mulūk by highlighting the relationship between the hadith tradition and the construction of classical Islamic history. This research departs from the methodological problem of early Islamic historiography which relies on narration, especially the use of sanad as the basis for the legitimacy of historical truth. The research method used is qualitative with a historical-textual approach and content analysis. This study does not dissect the entire volume of Tārīkh al-Rusul wa al-Mulūk, but focuses on the purposive textual samples in the early part of the book, particularly the narrations of Qabil and Habil, which show the use of sanad, the plurality of versions of the narration, and the differences in the matans in a single event. The data were analyzed through four categories, namely the structure of the sanad, the content of the matan, the narrative presentation pattern, and the methodological attitude of al-Ṭ abarī towards different narrations. The results of the study show that al-Ṭ abarī positioned himself as a compiler historian who maintained the mandate of transmission by presenting various versions of history without always giving an explicit assessment of the matan. This approach confirms that the historiography of al-Ṭ abarī operates within a framework of classical Islamic epistemology that prioritizes sanad authority over historical causality analysis. On the one hand, this model reinforces the integrity of transmission and opens up a space of plurality of historical narratives; On the other hand, he presents methodological limitations in the form of inconsistent internal criticism of the content of history. The novelty of this article lies in the reading of sanad not only as an instrument of verification, but also as a narrative strategy and legitimacy of scholarly authority in classical Islamic historiography. These findings enrich the discourse of Islamic historiography by placing al-Ṭ abarī's work as an epistemological transition space between the hadith tradition and systematic historical writing.